Advances in precise single-cell capture for analysis and biological applications. Issue 32 (10th August 2022) - Wang, Xiaowen; Wang, Zhen; Yu, Chang; Ge, Zhixing; Yang, Wenguang
Abstract : In this review, the category of technologies to capture single cells and their latest applications are summarized. Finally, some perspectives are provided on current development trends, future research directions, and challenges of single-cell capture. Abstract : Cells are the basic structural and functional units of living organisms. However, conventional cell analysis only averages millions of cell populations, and some important information is lost. It is essential to quantitatively characterize the physiology and pathology of single-cell activities. Precise single-cell capture is an extremely challenging task during cell sample preparation. In this review, we summarize the category of technologies to capture single cells precisely with a focus on the latest development in the last five years. Each technology has its own set of benefits and specific challenges, which provide opportunities for researchers in different fields. Accordingly, we introduce the applications of captured single cells in cancer diagnosis, analysis of metabolism and secretion, and disease treatment. Finally, some perspectives are provided on the current development trends, future research directions, and challenges of single-cell capture.